2023
DOI: 10.1007/s11739-023-03251-6
|View full text |Cite
|
Sign up to set email alerts
|

Are smart glasses feasible for dispatch prehospital assistance during on-boat cardiac arrest? A pilot simulation study with fishermen

Abstract: The aim of the study was to explore feasibility of basic life support (BLS) guided through smart glasses (SGs) when assisting fishermen bystanders. Twelve participants assisted a simulated out-of-hospital cardiac arrest on a fishing boat assisted by the dispatcher through the SGs. The SGs were connected to make video calls. Feasibility was assessed whether or not they needed help from the dispatcher. BLS-AED steps, time to first shock/compression, and CPR’s quality (hands-only) during 2 consecutive minutes (1s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In one study which compared chest compression quality performed by individuals wearing and not wearing the glasses, there was no significant difference, however, there was improvement in the ability of glasses wearers to complete the basic life support (BLS) protocol, open an airway, check breathing, position AED pads, and deliver a shock [54]. These results were echoed by another pilot study which found that CPR quality was not improved with the usage of smart glasses but did note that out of 96 skills that were assessed using the smart glasses, assistance by the dispatcher was given in 65 steps (72% of interventions) with the majority of the assistance related to AED usage [55].…”
Section: Smart Devicesmentioning
confidence: 99%
“…In one study which compared chest compression quality performed by individuals wearing and not wearing the glasses, there was no significant difference, however, there was improvement in the ability of glasses wearers to complete the basic life support (BLS) protocol, open an airway, check breathing, position AED pads, and deliver a shock [54]. These results were echoed by another pilot study which found that CPR quality was not improved with the usage of smart glasses but did note that out of 96 skills that were assessed using the smart glasses, assistance by the dispatcher was given in 65 steps (72% of interventions) with the majority of the assistance related to AED usage [55].…”
Section: Smart Devicesmentioning
confidence: 99%